Expression of Potato StDRO1 in Arabidopsis Alters Root Architecture and Drought Tolerance - Sun, C.; Liang, W.; Yan, K.; Xu, D.; Qin, T.; Fiaz, S.; Kear, P.; Bi, Z.; Liu, Y.; Liu, Z.; Zhang, J.; Bai, J. (Frontiers Media, 2022)
Potato (Solanum tuberosum L) is the third important crop for providing calories to a large human population, and is considered sensitive to moderately sensitive to drought stress conditions. The development of drought-tolerant, elite varieties of potato is a challenging task, which can be achieved through molecular breeding. Recently, the DEEPER ROOTING 1 (DRO1) gene has been identified in rice, which influences plant root system and regulates grain yield under drought stress conditions. The potato StDRO1 protein is mainly localized in the plasma membrane of tobacco leaf cells, and overexpression analysis of StDRO1 in Arabidopsis resulted in an increased lateral root number, but decreased lateral root angle, lateral branch angle, and silique angle. Additionally, the drought treatment analysis indicated that StDRO1 regulated drought tolerance and rescued the defective root architecture and drought-tolerant phenotypes of Atdro1, an Arabidopsis AtDRO1 null mutant. Furthermore, StDRO1 expression was significantly higher in the drought-tolerant potato cultivar “Unica” compared to the drought-sensitive cultivar “Atlantic.” The transcriptional response of StDRO1 under drought stress occurred significantly earlier in Unica than in Atlantic. Collectively, the outcome of the present investigation elucidated the role of DRO1 function in the alternation of root architecture, which potentially acts as a key gene in the development of a drought stress-tolerant cultivar. Furthermore, these findings will provide the theoretical basis for molecular breeding of drought-tolerant potato cultivars for the farming community.